FABRICATION OF SILVER NANOPARTICLES: USING VITEX NEGUNDO L. AGAINST CISPLATIN-INDUCED NEPHROTOXICITY IN ALBINO RAT - M, Janakiraman (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was carried out to evaluate the fabrication of silver nanoparticles using Vitex negundo L. against cisplatin-induced nephrotoxicity in albino rat. Methods: Synthesized silver nanoparticles of V. negundo L. were characterized by particle size, ultra violet (UV)-visible, Fourier transform infrared (FTIR), and X-ray diffraction (XRD) analysis. Albino rats were divided randomly into six groups of six animals each. Group I normal rats were treated with an oral dose of distilled water for 15 days. Group II rats were treated with single i.p. dose of cisplatin (16 mg/kg) on day 1. Group III rats were treated only with an oral dose of V. negundo L. (200 mg/kg/d) for 15 days. Group IV rats were treated only with an oral dose of silver nanoparticles of V. negundo L. (200 mg/kg/d) for 15 days. Group V rats were treated with an oral dose of V. negundo L. for 14 days after single i.p. dose of cisplatin on day 1. Group VI rats were treated with an oral dose of silver nanoparticles of V. negundo L. for 14 days after single i.p. dose of cisplatin on day 1. Collected blood samples and kidney tissue samples were used for biochemical, enzymatic antioxidant, and histopathological studies in all groups. Results: The formation of silver nanoparticles was confirmed by particle size, UV-visible, and XRD analysis, and active principles were identified by FTIR analysis. Biochemical results of silver nanoparticles of V. negundo L.-treated groups showed the significant (pË‚0.05) decrease in the level of creatinine, urea, and uric acid as compared to cisplatin-induced rats. The enzymatic antioxidants results of silver nanoparticles of V. negundo L.-treated groups showed the significant (pË‚0.05) increase in the level of glutathione reductase and significant decrease in malondialdehyde level as compared to cisplatin-induced rats. In addition, histopathological results of silver nanoparticles of V. negundo L.-treated groups showed the ameliorated impact in cisplatin-induced rats. Conclusion: The results of these studies were concluded that silver nanoparticles of V. negundo L. have profound protective effect against the adverse effects caused by cisplatin in rat kidney than V. negundo L. treated along with cisplatin in albino rat.